DNA adducts as a measure of lung cancer risk in humans exposed to polycyclic aromatic hydrocarbons. - Kriek, E (1993)
Workers in the coking, foundry, and aluminum industry can be exposed to high concentrations of polycyclic aromatic hydrocarbons (PAHs) and are at increased risk for lung cancer, as are cigarette smokers. In recent years several studies on workers in the foundry and coking industries have been reported. In these studies, white blood cell(WBC) DNA was used for analysis of PAH-DNA adducts. Theoretically, DNA adduct formation is a more relevant biological parameter for assessing exposure risk than PAH in the work atmosphere, or the amount of a metabolite in the urine, because adduct levels reflect that part of the dose that escapes detoxification and binds to DNA. We analyzed WBC DNA from coke-oven workers and from workers in an aluminum production plant and demonstrated the presence of PAH-DNA adducts. Forty-seven percent of the coke-oven workers had detectable levels of PAH-DNA adducts in their WBC compared with 27% of the controls (p < 0.05), measured with ELISA. In both groups, smokers had significantly higher levels of PAH-DNA adducts than did nonsmokers. In the aluminum workers, no PAH-DNA adducts were detected by ELISA, although the benzo[a]pyrene concentrations in the work atmosphere were comparable to those of the coke-oven workers. The more sensitive 32P-postlabeling assay showed the presence of PAH-DNA adducts in 91% of the aluminum workers. There was no correlation of WBC adduct levels with the concentration of PAH in the work atmosphere. Recently we showed that total PAH-DNA adduct levels in WBC from lung cancer patients were much higher than those generally found in healthy smokers.(ABSTRACT TRUNCATED AT 250 WORDS)